Employee Performance in Generation Y: Is Organizational Commitment Matters? - Lela Lestari; Indi Djastuti (Jurnal REKOMEN (Riset Ekonomi Manajemen), 2023)
Generation Y or millennial This research focuses on the discussion of organizational commitment as a variable that affects the performance of generation Y or millennial employees in State-owned enterprises. The sample was determined using the purposive sampling method and the number of respondents in this study was 139 employees in Indonesia. The technique used to collect data from respondents is a questionnaire, then the analysis model used component-based SEM (structural equation model). This study found that organizational commitment has negatively related to employee performance. Furthermore, organizational commitment is not proven to acts as a mediator variable of the relationship between job characteristics and transformational leadership on employee performance.